Effects of polyunsaturated fatty acids on gastric cancer immunity and immunotherapy - Dikan Wu; Fan Fan; Junxian He; Lian Wang; Caiyun Zhu; Yalin Ji; Haijun Zhang (Scientific Reports)
Abstract Although immunotherapy has been predominant for advanced gastric cancer treatment, it still has limitations. Polyunsaturated fatty acids (PUFAs) are associated with inflammation while their roles in tumor immune microenvironment (TIME) are unclear. This study explores PUFAs’ impacts on gastric cancer immunity and immunotherapy efficacy. Bioinformatics analysis was conducted to identify differential expressions of PUFAs metabolic genes and their immune correlations. Clinical data of advanced gastric cancer patients receiving immunotherapy at Zhongda Hospital (2020–2024), whose serum PUFAs were measured by mass spectrometry (MS), were collected and analyzed. Bioinformatics analysis revealed differential expression of half of PUFAs metabolic genes in gastric cancer. PUFAs metabolism towards Omega-3 (ω-3) tended to increase infiltration of active anti-tumor cells and up-regulate multiple immune checkpoints expressions, while metabolism towards Omega-6 (ω-6) led to opposite TIME outcomes. The clinical study demonstrated that lower serum ω-6/ω-3 ratio, arachidonic acid/eicosapentaenoic acid (AA/EPA) ratio, linoleic acid/alpha-linolenic acid (LA/ALA) ratio and higher EPA were associated with better six-month progression-free survival rate (6-month PFS) and one-year overall survival rate (1-year OS). This study deepens our understandings of TIME in gastric cancer. It clearly demonstrates that maintaining appropriate PUFAs ratios or values is promising in improving prognosis.